Current status and future recommendations for feral swine disease surveillance in the United States. (5th February 2019) - Brown, Vienna R; Marlow, Michael C; Maison, Rachel M; Gidlewski, Thomas; Bowen, Richard; Bosco-Lauth, Angela
Abstract: USDA APHIS Wildlife Services (WS ) responded to the threat of feral swine as a pathogen reservoir as early as 2004. To increase awareness and knowledge on that risk, WS began opportunistic sampling of animals harvested by its operational component to curtail swine damage to agriculture and property. Initially, pseudorabies and swine brucellosis were of most concern, as both serve as a potential threat to the domestic swine industry and the latter also possesses zoonotic implications. In 2006, classical swine fever, a foreign animal disease, became the main driver for feral swine pathogen surveillance. Subsequent years of surveillance identified numerous other disease risks inherent within populations of feral swine. Presently, feral swine surveillance falls under the purview of the APHIS National Feral Swine Damage Management Program, which began in 2014. In January 2018, a panel of animal disease experts representing industry, government, and academia were invited to Fort Collins, Colorado to discuss successes of this surveillance, identify any shortcomings or needs, and propose future feral swine surveillance. This manuscript serves to synthesize WS' surveillance and the future direction of these efforts.